Selective and sensitive fluorescent and colorimetric chemosensor for detection of CO32- anions in aqueous solution and living cells - Elmas, Sukriye Nihan Karuk; Ozen, Furkan; Koran, Kenan; Gorgulu, Ahmet Orhan; Sadi, Gokhan; Yilmaz, Ibrahim; Erdemir, Serkan (Elsevier, 2018)
A new colorimetric and fluorescent chemosensor for visual determination of carbonate ions was developed by the microwave assisted solvent free synthesis of 7,8-dihydroxy-3-(4-methylphenyl) coumarin (DHMC). The structural characterization of DHMC was confirmed by microanalysis and spectroscopy methods (MALDI-TOF, FT-IR, H-1 NMR, C-13 NMR, and 2D HETCOR). The binding behaviors of DHMC were investigated towards various anions by UV-vis and fluorescence spectroscopy. DHMC showed a selective and sensitive fluorometric and colorimetric responses towards carbonate ion over other anions. The detection limit of CO32- was found to be 1.03 mu M. Moreover, the fluorescence imaging in living cells suggests that DHMC has a great potential in the biological imaging application. It has been demonstrated that DHMC can be used as a rapid and reliable sensor for the determination of carbonate anion in a variety of practical applications.
Keywords: Chemosensor; Coumarin; Carbonate; Molecular sensing; Fluorescent sensor